Le coton à El Deir - Fleur Letellier-Willemin (Revue d'ethnoécologie)
The presence of cotton in el-Deir (Kharga oasis, Egyptian Western desert) is a recent archaeological discovery, mainly of funerary origin. Despite its relative rarity, cotton and its study show the existence of different textile categories, distinguished by varied degrees of quality and diverse usages. It is also interesting to observe the evolution of cotton’s quality on the site, comparing it to other – better attested – fibres, such as linen and wool. This new fibre sheds a new light of the daily life of the inhabitants, their funerary practices, their economy, and implies possible changes in agricultural management and trade patterns during Antiquity (5th c. BCE-5th c. CE).